Terror: the danger of legal theatre - Markéta Štěpáníková (Law Text Culture, 2021)
When Ferdinand von Schirach wrote Terror, a perfect example of the legal theatre was created. It is a trial or tribunal play that deals both with current legal issues and a profound legal-philosophical dilemma of sacrificing human lives for the lives of others. Moreover, this play provides a space for the audience to express their legal opinion in a very theatrical way. In a sense, this play refers to the roots of ancient Greek theatre (see eg Gaakeer 2019) and its fundamentally political meaning. Thus, it may seem that this play is an answer to every law and theatre scholar’s prayer for a practical example of a widely know trial play. Unfortunately, it is more complicated than that. In a way, any theatre about law – legal theatre – is political theatre. Through its influence, legal theatre can pose consequences for the rule of law and democracy. In this text, I will focus on the specifics of legal theatre and its possible consequences. My research takes the form of a case-study of Ferdinand von Schirach’s play Terror. For comparison, another legal theatre play will be used: Milada. Milada is a documentary theatre play based on a real political trial concerning Milada Horáková in the 1950s in Czechoslovakia. Through the analysis of both plays, I will determine and explain the most problematic issues. This issues are, of course, too broad to deal with in one paper, so I will focus on the question of ‘reality’ in the presentation of law in both plays and its possibly dangerous consequences, especially in the geographical area of Central Europe.